Voluntariness of consent in paediatric HIV clinical trials: a mixed- methods, cross- sectional study of participants in the CHAPAS- 4 and ODYSSEY trials in Uganda - Makumbi, Shafic; Bajunirwe, Francis; Ford, Deborah; Turkova, Anna; South, Annabelle; Lugemwa, Abbas; Musiime, Victor; Gibb, Diana; amwesigire, Imelda K T (BMJ Open, 2024)
Objectives: To examine the voluntariness of consent in paediatric HIV clinical trials and the associated factors. Design: Mixed- methods, cross- sectional study combining a quantitative survey conducted concurrently with in depth interviews. Setting and participants: From January 2021 to April 2021, we interviewed parents of children on first- line or second- line Anti- retroviral therapy (ART) in two ongoing paediatric HIV clinical trials [CHAPAS- 4 (ISRCTN22964075) and ODYSSEY (ISRCTN91737921)] at the Joint Clinical Research Centre Mbarara, Uganda. Outcome measures The outcome measures were the proportion of parents with voluntary consent, factors affecting voluntariness and the sources of external influence. Parents rated the voluntariness of their consent on a voluntariness ladder. In depth interviews described participants’ lived experiences and were aimed at adding context. Results: All 151 parents randomly sampled for the survey participated (84% female, median age 40 years). Most (67%) gave a fully voluntary decision, with a score of 10 on the voluntariness ladder, whereas 8% scored 9, 9% scored 8, 6% scored 7, 8% scored 6 and 2.7% scored 4. Trust in medical researchers (adjusted OR 9.90, 95% CI 1.01 to 97.20, p=0.049) and male sex of the parent (adjusted OR 3.66, 95% CI 1.00 to 13.38, p=0.05) were positively associated with voluntariness of consent. Prior research experience (adjusted OR 0.31, 95% CI 0.12 to 0.78, p=0.014) and consulting (adjusted OR 0.25. 95% CI 0.10 to 0.60, p=0.002) were negatively associated with voluntariness. Consultation and advice came from referring health workers (36%), spouses (29%), other family members (27%), friends (15%) and researchers (7%). The in depth interviews (n=14) identified the health condition of the child, advice from referring health workers and the opportunity to access better care as factors affecting the voluntariness of consent. Conclusions: This study demonstrated a high voluntariness of consent, which was enhanced among male parents and by parents’ trust in medical researchers. Prior research experience of the child and advice from health workers and spouses were negatively associated with the voluntariness of parents’ consent. Female parents and parents of children with prior research experience may benefit from additional interventions to support voluntary participation
Keywords: Voluntariness; Paediatrics; HIV clinics; Uganda